ADVANCED NEONATAL SCREENING IN TASHKENT: FIRST RESULTS AND EFFECTIVENESS ANALYSIS (Web of Teachers: Inderscience Research, 2025)
The thesis presents the first results and organizational experience of the implementation of the pilot program of expanded neonatal screening (RNS) in the city of Tashkent.